1996
DOI: 10.1016/s0022-5223(96)70449-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of competitive blood flow on arterial graft patency and diameter

Abstract: To identify predictors of arterial graft patency, we followed up 30 internal thoracic arterial grafts and 23 right gastroepiploic arterial grafts in situ with patency documented during postoperative angiography. After 24 months of follow-up on average, repeat angiography detected that one internal thoracic artery and two gastroepiploic arteries were anatomically occluded and that the other three gastroepiploic arteries were nonfunctioning. The logistic regression model identified a relationship between graft p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
4

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 23 publications
1
40
0
4
Order By: Relevance
“…Doppler studies have suggested that moderate stenosis in the target vessel is associated with competitive flow, thereby leading to decreased antegrade flow in the arterial graft, which may lead to early failure (string sign). [13][14][15] Recently, Berger et al reported that the degree of stenosis in the native vessel is a major predictor of ITA graft occlusion. 17) The ITA was anastomosed to the LAD in 96% of our recent CABG cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doppler studies have suggested that moderate stenosis in the target vessel is associated with competitive flow, thereby leading to decreased antegrade flow in the arterial graft, which may lead to early failure (string sign). [13][14][15] Recently, Berger et al reported that the degree of stenosis in the native vessel is a major predictor of ITA graft occlusion. 17) The ITA was anastomosed to the LAD in 96% of our recent CABG cases.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] However, it has been suggested that mild or moderate stenosis in the LAD is associated with competitive flow, thereby leading to a decreased antegrade flow in the ITA graft, which may lead to graft failure. [13][14][15][16] The purpose of this study was to evaluate the influence of clinical parameters and the degree of LAD stenosis on postoperative ITA graft stenosis, as well as the relationship between postoperative regional ischemia of the LAD territory, as assessed by adenosine thallium-201 myocardial perfusion scintigraphy (Tl-201-MPS), and postoperative ITA graft stenosis using 320-ADCT.…”
Section: Introductionmentioning
confidence: 99%
“…4) In the cases with bilateral ITA grafts, the contralateral ITA, which was grafted to a severely stenotic vessel, was widely patent. Hashimoto, et al 11) followed 30 LITA and 23 gastroepiploic artery grafts for a mean of 24 months. Stenosis of the recipient artery was significantly more severe in functioning grafts than in nonfunctioning ones.…”
Section: Discussionmentioning
confidence: 99%
“…For example, as noted, early graft failures in the form of "string sign" have been noted in randomized trials [78], and several explanations for this are possible. For example, RA grafts appear notoriously susceptible to competitive flow within the native coronary circulation, as may occur when native coronary stenosis is not severe ( 70%) [128,129]. Based on this frequent observation, use of the RA is not recommended as a conduit for CABG unless the native coronary artery stenosis is high grade ( 70%).…”
Section: Radial Arterymentioning
confidence: 99%